Determinants Of Interest In Using The E-Wallet Application (Case Study on UBL Accounting Students) - Rada Ameka; Riswan Riswan; Haninun Haninun (Cita konsultindo, 2024)
The use of e-wallet applications, which are currently widely used for transactions and replace cash payments, is the background of this study. This study aims to determine the effect of perceived benefits and convenience on interest in using e-wallet applications and the role of perceived usefulness in mediating the effect of perceived benefits and perceived convenience on interest in using e-wallet applications. This study uses a quantitative approach using primary data obtained through the distribution of questionnaires. The population in this study were all students of the Faculty of Economics and Business, Bandar Lampung University, Accounting study program. The sample in this study were students who actively transacted using e-wallets. The result is that perceived benefits have an insignificant effect on interest in using the e-wallet application, while perceived convenience has a positive and significant impact on interest in using the e-wallet application. And perceived usefulness is able to mediate the effect of perceived benefits and perceived convenience on interest in using e-wallet applications. It can be concluded that the easier it is to use the e-wallet application, the stronger the user's attractiveness and encourage interest in using the e-wallet application.